Dc glow discharge for synthesis diamond films with high growth rate - Gritsyna, V.I.; Opalev, O.A.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2019)
The results of experiments on further investigation of the growth kinetics of diamond films in a dc glow discharge on modernized equipment are presented. As a result of the research, it was possible to expand the possibilities of using equipment for the synthesis of diamond films in a glow discharge with a grounded substrate holder. The diamond film growth rates were 3-4 times higher than those obtained in earlier experiments while maintaining high structural characteristics of the synthesized diamond film. The maximum growth rate was 12 μm/h at the pressure of the hydrogen-methane mixture in the discharge chamber of 180 mm Hg. The possibility of obtaining both polycrystalline diamond films without pronounced texture and high-textured diamond films with an orientation of the surface of diamond crystallites (100) parallel to the sample surface is demonstrated. Thus, the presented hydrogen-methane mixture activation system for the synthesis of diamond films is promising for use in technological applications.